Evaluation of clinical ethics support services and its normativity. Issue 11 (17th January 2013) - Schildmann, Jan; Molewijk, Bert; Benaroyo, Lazare; Forde, Reidun; Neitzke, Gerald
Abstract : Evaluation of clinical ethics support services (CESS) has attracted considerable interest in recent decades. However, few evaluation studies are explicit about normative presuppositions which underlie the goals and the research design of CESS evaluation. In this paper, we provide an account of normative premises of different approaches to CESS evaluation and argue that normativity should be a focus of considerations when designing and conducting evaluation research of CESS. In a first step, we present three different approaches to CESS evaluation from published literature. Next to a brief sketch of the well-established approaches of 'descriptive evaluation' and 'evaluation of outcomes', we will give a more detailed description of a third approach to evaluation—'reconstructing quality norms of CESS'—which is explicit about the normative presuppositions of its research (design). In the subsequent section, we will analyse the normative premises of each of the three approaches to CESS evaluation. We will conclude with a brief argument for more sensitivity towards the normativity of CESS and its evaluation research.